The Changing Paradigm of Head and Neck Paragangliomas: What Every Otolaryngologist Needs to Know. (November 2020) - Cass, Nathan D.; Schopper, Melissa A.; Lubin, Jonathan A.; Fishbein, Lauren; Gubbels, Samuel P.
Background: Recommendations regarding head and neck paragangliomas (HNPGL) have undergone a fundamental reorientation in the last decade as a result of increased understanding of the genetic and pathophysiologic basis of these disorders. Objective: We aim to provide an overview of HNPGL and recent discoveries regarding their molecular genetics, along with updated recommendations on workup, treatment, and surveillance, and their implications for otolaryngologists treating patients with these disorders. Results: SDHx susceptibility gene mutations, encoding subunits of the enzyme succinate dehydrogenase (SDH), give rise to the Hereditary Pheochromocytoma/Paraganglioma Syndromes. SDHA, SDHB, SDHC, SDHD, and SDHAF2 mutations each result in unique phenotypes with distinct penetrance and risk for variable tumor development as well as metastasis. Genetic and biochemical testing is recommended for every patient with HNPGL. Multifocal disease should be managed in multi-disciplinary fashion. Patients with SDHx mutations require frequent biochemical screening and whole-body imaging, as well as lifelong follow-up with an expert in hereditary pheochromocytoma and paraganglioma syndromes. Conclusion: Otolaryngologists are likely to encounter patients with HNPGL. Keeping abreast of the latest recommendations, especially regarding genetic testing, workup for additional tumors, multi-disciplinary approach to care, and need for lifelong surveillance, will help otolaryngologists appropriately care for these patients.